RECONSTRUCTING EDUCATIONAL INNOVATION A CONCEPTUAL REVIEW OF CRITICAL PHILOSOPHY PERSPECTIVE BASED ON SOCIAL ISSUE - Ai Solihah; Ufiya Putri Adhiyati; Henny Suharyati (Cakrawala Pedagogik, 2026)
The dominant discourse of educational innovation largely technocratic and market-oriented—tends to neglect emancipatory dimensions, social justice, and the humanization of learners. This condition calls for a more critical philosophical inquiry to reframe how educational innovation is understood. This study aims to reconstruct the concept of educational innovation from the perspective of critical philosophy so that innovation is not merely conceived as a technical improvement, but as a project of liberation and humanization of learners. Employing a qualitative approach, this research adopts a conceptual review design through an in-depth literature study of critical philosophy, philosophy of education, and educational innovation discourse. The primary data sources include books, journal articles, and policy documents that explicitly address critical theory and educational innovation. The analysis proceeded in three stages: identifying key concepts, critically examining the ideological assumptions underpinning mainstream innovation discourse, and reconstructing a conceptual framework of educational innovation grounded in emancipation, dialogue, and social justice. The findings indicate that mainstream educational innovation remains dominated by instrumental rationality and market logics; therefore, it must be reoriented toward innovation that affirms education as a space for forming critical and emancipatory subjects. This study concludes that reconstructing educational innovation within critical philosophy requires a paradigm shift from efficiency- and performativity-driven innovation toward innovation oriented to dialogue, equality, and human emancipation. Theoretically, this study contributes a critical-philosophy-based conceptual framework that may serve as a reference for policymakers, researchers, and educational practitioners in designing more humanistic and transformative innovations.